ANALISIS FITOKIMIA AIR REBUSAN DAUN KAYU JAWA (Lannea coromandelica) - Fadliah, Sarah; Mu'nisa, Andi; Rachmawaty, R. (Fakultas MIPA UNM, 2018)
Abstract. Indian Ash Tree (Lannea coromandelica) is a native plant from Indian and empirically used for pain remedy. The leaves were simply applied on the affected area for external wound, then for internal wound in a way boil the leaves and drink it. The chemical composition of medical plant determined its pharmacology. This research explored the potency of (Lannea coromandelica) by determining its secondary metabolites group. The plant was collected from Makassar, South Sulawesi. The results showed that (Lannea coromandelica) was positive for Saponins, Flavonoids, polifenols and Tannins.Keyword : Indian Ash Tree leaves, Phytochemical, Medical plant.